Mind Map Sebuah Metode Solutif Meringkas Materi Pelajaran Berbasis Visual : (Pendampingan Strategi Pembelajaran di SD Sukosari Mantup Lamongan) - Nanang Abdillah; Rahmat Rudianto; Kharisma Putri Dwi Anggraeni; Zaenal Afandi; Charis Daffa Sabilillah; Menok Faiqatul Himmah; Jauharotul Munawaroh; Salfa Rizqi Amalia; Ahmad Nuzulul Furqon; Diva Vicky Viera (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The abstract of this research discusses Mind Map learning assistance as a method to facilitate visual-based summary of lesson material for Sukosari Mantup Lamongan Elementary School students. The Mind Map method was chosen because of its ability to improve students' understanding and memory through information visualization. Mentoring activities are carried out in three stages: preparation, implementation and evaluation. In the preparation stage, the service team prepares the necessary materials and tools. During implementation, students are taught how to make Mind Map s using concrete examples, so they can understand how to summarize material effectively. The results of this activity show that students are able to summarize the material better using the Mind Map method. Students' enthusiasm increases, and they demonstrate better abilities in understanding and summarizing lesson information. This research concludes that the use of Mind Map as a learning method has a positive impact on the teaching and learning process in the classroom, and can be an interesting alternative for students in understanding lesson material visually.